Information Technology as a Promotion Agent - M F A Sudistira; M F Nasruddin (Universitas Komputer Indonesia, 2021)
The purpose of this study is to see how promotions are carried out on social media as a marketing agent at this time. This research used a descriptive method by observing internet user behavior and analyzing the marketing strategy of Instagram as one of the platform social media that effectively as a promotion agent. The results of this paper show that many business people use various social media platforms as a medium to promote the products they offer. It is because, in the current era, social media is a medium that is widely used by large communities in various parts of the world. With various facilities and also minimal costs, making social media widely used by business people with attractive offers and affordable prices.